Elbow hemiarthroplasty in distal humeral fractures: Indication, surgical technique and results. (March 2023) - Rotini, Roberto; Ricciarelli, Marco; Guerra, Enrico; Marinelli, Alessandro; Celli, Andrea
Highlights: Open reduction internal fixation is sometimes impossible in distal humerus fractures in adults due to extensive comminution and bone loss. Elbow Hemi-Arthroplasty (EHA) is a reasonable option for unreconstructible intra-articular distal humerus fractures in patients over the fifth decade. The implant removes complications related to the ulnar component such as wear of the hinge or aseptic loosening of the ulnar component. It does bring potential disadvantages such as risk of instability with possible wear and progressive joint osteoarthrosis. Abstract: The surgical management of distal humerus fractures in adults generally consists in open reduction internal fixation (ORIF) or total elbow arthroplasty (TEA). Hemi humeral hemiarthroplasty (EHA) is a treatment option for unreconstructable intra-articular distal humerus fractures. It is a reasonable option in patients over the fifth decade and its potential advantages are to eliminate the complications related to the ulnar component such as wear of the hinge (busching wear) or the aspetic loosening of the ulnar component. The potential disadvantages are the risk of instability with the possibility of a wear and progressive joint osteoarthrosis. The aims of this manuscript are to evaluate the indications in which we used the EHA, analyzing the correct surgical technique and describe the outcomes in medium and long-term follow-ups. Between 2006 and 2019, we performed 51 EHAs at the Hesperia Hospital in Modena and at the Rizzoli Orthopedic Institute. Taking into consideration only the cases of acute fractures, 27 patients (27 elbows) with a minimum follow-up of 12 months were identified. The patient's mean age at the time of surgery was 64 years old (range from 45 to 78 years old) and they were 78% female (21 out of 27). The Latitude Tornier implant was used in all the patients of our group. The mean MEPS was 89.3 points (from 50 to 100 pts) with excellent results in 19 patients, good in 5, one fair and 2 poor;the mean DASH was 12.6 (from 3.3 to 45.8); the mean OES was 42.3 (from 22 to 47). Complications, were found in 12 patients and any patients required a TEA conversion. Distal humerus hemiarthroplasty from our experience is a good option for the surgical management of unrecostructible distal humeral fractures in selected patients. It is important to perform a precise surgical technique; preserve the triceps insertion, preserve or repair the collateral ligaments, fix the condylar bones implant the prosthesis at the correct size, depth and rotation. The majority of the complication that we observed are related to the stiffness and not to the progressive degenerative changes of the articular surface